Effectiveness of Planned Teaching Program on Knowledge Regarding Obstetric Triage among Final Year BSc Nursing Students of Selected Nursing Colleges, Mangaluru - Shashikala .; Bibi Augustin (RGUHS Journal of Nursing Sciences)
Background and aim Obstetric triage facilitates timely management of emergency cases. Obstetric triage can be counted as the best approach to reduce the length of hospital stay for increasing patient satisfaction reducing unnecessary admissions decreasing maternal and foetal mortality thereby improving obstetric care services. The present study aimed to determine the effectiveness of an education intervention program on knowledge about obstetric triage.Methods In the present study a two-group pre-test post-test quasi experimental research design was adopted. Eighty final year BSc nursing students were selected using convenient sampling technique from few select nursing colleges in Mangaluru. The pretest was conducted using a validated knowledge questionnaire following which educational intervention was administered for students in the experimental group. Subsequently a post intervention test was conducted after eight days using the same tool for all the students. Data analysis was done using Chi-square Fisher exact paired and unpaired lsquotrsquo tests.Results The study results confirmed that the educational intervention program was successful in improving the knowledge of nursing students. In the experimental group the mean pretest and post test scores were 11.73plusmn3.493 and 20.75plusmn3.774 respectively. In the control group the mean pre and post test scores were 13.28plusmn3.530 and 13.23plusmn2.370 respectively. There was a statistically significant difference in the overall knowledge scores between experimental and control groups P 0.001. There was no significant relationship between the socio demographic factors and the pre-test scores of experimental and control groups.Conclusion The current study revealed that the educational intervention program was more effectual in increasing the knowledge among nursing students and recommends that obstetric triage can be considered to be included in the nursing curriculum.